URGENSI PEMASARAN DIGITAL DALAM MENINGKATKAN DAYA BELI KONSUMEN TERHADAP PRODUK USAHA MIKRO, KECIL DAN MENENGAH ( UMKM ) DI KABUPATEN OKU TIMUR - Winda Feriyana; Agus Setiawati; Tedy Haryadi; Teti Liana (JURNAL ILMIAH EDUNOMIKA, 2026)
This study examines the crucial role of marketing in increasing sales turnover of Micro, Small, and Medium Enterprises (MSMEs) in East OKU Regency. This article outlines effective marketing strategies, including the implementation of digital marketing, branding, appropriate pricing strategies, and the role of promotions in increasing consumer purchasing power. A literature review found that implementing appropriate digital marketing strategies can significantly increase MSME visibility and optimize their sales performance. The results indicate that by utilizing social media platforms, MSMEs can reach a wider market, strengthen interactions with consumers, and create new business opportunities, and are known to experience turnover increases of up to 50%. This study also highlights the importance of government support and collaborative efforts to improve MSME access to marketing training and information. It is hoped that this article will provide useful insights for MSMEs and relevant local stakeholders to develop more effective and sustainable marketing strategies in an effort to support the ongoing digital transformation of MSMEs. Keywords : Digital Marketing, Purchasing Power, MSMEs